1988
DOI: 10.1530/acta.0.1180154
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous degradation of biosynthetic human growth hormone in growth hormone deficient patients

Abstract: The aim of the present study was to look further into the question of local degradation of sc injected human GH in GH deficient patients. A comparison was made of serum GH levels after constant iv and sc infusion of the same amount of GH (33 ng\m=.\ k g \ m = -\ 1 \ m = . \ m i n \ m = -\ 1 ) in the same 9 GH deficient patients. A 3-h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Interference of antibodies to GH produced locally in the subcutis might be suggested, but antibodies occur uncommonly with the GH preparations used today [7]. Alternatively, an impaired ability of some assays to recognize the GH molecule due to alteration of the immunoreactivity of the molecule during its passage through the sc tissue compartment might explain the observed reduced apparent bioavailability of GH following sc administration [218]. In a study in ten GHD patients, in whom GH therapy had been discontinued for five days before the study, GH was administered as a continuous infusion for 39 h in a crossover design [69].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Interference of antibodies to GH produced locally in the subcutis might be suggested, but antibodies occur uncommonly with the GH preparations used today [7]. Alternatively, an impaired ability of some assays to recognize the GH molecule due to alteration of the immunoreactivity of the molecule during its passage through the sc tissue compartment might explain the observed reduced apparent bioavailability of GH following sc administration [218]. In a study in ten GHD patients, in whom GH therapy had been discontinued for five days before the study, GH was administered as a continuous infusion for 39 h in a crossover design [69].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…3,4,61,62 Subcutaneous degradation has been specifically suggested for several proteins including hGH, 63,64 erythropoietin (EPO), 3,65 and insulin, [66][67][68] however, direct experimental evidence for this putative mechanism is limited. For example, whilst aprotinin, a serine protease inhibitor, has been reported to enhance the rate and extent of absorption of parathyroid hormone, 69 calcitonin, 69 and insulin, …”
Section: Absorption Of Proteins After Sc Administrationmentioning
confidence: 99%
“…Jorgensen et al also attributed differences in steady state serum concentrations following SC and IV infusions to degradation of hGH at the SC injection site. 6 Two more recent studies reported that the systemic availability of hGH following a single SC injection 7 and a continuous SC infusion, 8 each relative to an IV control, was 49.5% and 70.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%